2023
DOI: 10.3390/membranes13090791
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Performance of Spiral-Wound Modules (SWMs) by Improving Stability against Axial Pressure Drop and Utilising Pulsed Flow

Christian Kürzl,
Martin Hartinger,
Patrick Ong
et al.

Abstract: Spacer-induced flow shadows and limited mechanical stability due to module construction and geometry are the main obstacles to improving the filtration performance and cleanability of microfiltration spiral-wound membranes (SWMs), applied to milk protein fractionation in this study. The goal of this study was first to improve filtration performance and cleanability by utilising pulsed flow in a modified pilot-scale filtration plant. The second goal was to enhance membrane stability against module deformation b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…Simulation in CFD revealed a 57.9% increase in average minimum wall shear at the membrane surface with reduced fouling potential. Kürzl et al, 2023 worked on increasing the stability of the SWM module by implementing a glue connection in the membrane inlet, which showed increased volume throughput of>100% and also increased filtration and cleanability performance by 26% and 28% with pulsed flow (on/off bypass) around the membrane. Ji et al, 2024 demonstrated that implementing angular vibrations at a frequency of 15 Hz on the SWM module effectively controlled algal fouling by up to 28.5%, with a lower energy loss of 76.1 mW than the traditional increasing flow rate method.…”
Section: Spiral-wound Modulementioning
confidence: 99%
“…Simulation in CFD revealed a 57.9% increase in average minimum wall shear at the membrane surface with reduced fouling potential. Kürzl et al, 2023 worked on increasing the stability of the SWM module by implementing a glue connection in the membrane inlet, which showed increased volume throughput of>100% and also increased filtration and cleanability performance by 26% and 28% with pulsed flow (on/off bypass) around the membrane. Ji et al, 2024 demonstrated that implementing angular vibrations at a frequency of 15 Hz on the SWM module effectively controlled algal fouling by up to 28.5%, with a lower energy loss of 76.1 mW than the traditional increasing flow rate method.…”
Section: Spiral-wound Modulementioning
confidence: 99%